Galangin inhibited ferroptosis through activation of the PI3K/AKT pathway in vitro and in vivo. Issue 11 (2nd October 2022) - Chen, Ke; Xue, Ran; Geng, Yaping; Zhang, Shenshen
Abstract: Ferroptosis is an iron‐dependent form of nonapoptotic cell death characterized by the accumulation of lipid peroxides in cells. In recent years, extensive attention has been dedicated to exploring safe and effective natural ferroptosis regulators which can provide novel treatment strategies for ferroptosis‐related diseases. This study identified galangin, a natural flavonoid, as an effective inhibitor of ferroptosis, which could increase cell viability in RSL3‐inhibited HT1080 cells, decrease levels of lipid ROS and MDA, improve PTGS2 mRNA expression, and enhance the expression of glutathione peroxidase 4 (GPX4). Ferroptosis is widely present in ischemia‐reperfusion (IR) injury. This study found that galangin significantly ameliorated the pathological damage of liver tissue in mice with IR, reduced levels of serum ALT, AST, and MDA, and increased the expression of GPX4. The results of RNA‐seq exhibited ferroptosis was significant and the PI3K/AKT pathway deserved to explore the inhibition effects of galangin on ferroptosis. Indeed, galangin treatment significantly rescued RSL3‐inhibited phosphorylation levels of PI3K, AKT, and CREB proteins, and the ferroptosis inhibitory effects of galangin were counteracted by PI3K inhibitor LY294002. These findings indicated that galangin may exert its anti‐ferroptosis effects via activating the PI3K/AKT/CREB signaling pathway and it will hopefully serve as a promising effective measure to attenuate IR injury by inhibiting ferroptosis.